2012
DOI: 10.1515/jpem-2012-0121
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of subclinical hypothyroidism in 5- to 15-year-old children with migraine headache

Abstract: Based on the results of this study, subclinical hypothyroidism was as an exacerbating factor for migraine headache. Therefore, it is logical to check the thyroid function tests in migraineur children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 0 publications
3
25
0
2
Order By: Relevance
“…Most studies have reported an increased prevalence of hypothyroidism in persons with headache disorders . Many of these studies however have important methodological limitations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have reported an increased prevalence of hypothyroidism in persons with headache disorders . Many of these studies however have important methodological limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies however have important methodological limitations. First, many of the past studies used clinic‐based samples, which may not be representative of the general population. Second, some studies relied upon patient self‐report instead of hormone levels to establish a diagnosis of hypothyroidism, which may not provide an accurate diagnosis of the condition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Fallah et al performed a cross‐sectional study of children and adolescent migraineurs ages 5 to 15 years to determine the frequency of hypothyroidism in this population. They found approximately one‐quarter of the patients to have some degree of hypothyroidism and believed it to be an exacerbating factor for headaches . Another study by the same group found treatment of subclinical hypothyroidism with levothyroxine significantly decreased the frequency and severity of headaches in 25 pediatric migraineurs over 2 months…”
Section: Discussionmentioning
confidence: 98%
“…Small cross-sectional studies by Fallah et al and Ekici et al offered conflicting results in this regard. (131,132) …”
Section: Migrainementioning
confidence: 99%